2012
DOI: 10.1177/0095798412469227
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of General Social Support and Social Support for Racial Discrimination on African American Women’s Well-Being

Abstract: The present longitudinal study examined the role of general and tailored social support in mitigating the deleterious impact of racial discrimination on depressive symptoms and optimism in a large sample of African American women. Participants were 590 African American women who completed measures assessing racial discrimination, general social support, tailored social support for racial discrimination, depressive symptoms, and optimism at two time points (2001–2002 and 2003–2004). Our results indicated that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 48 publications
5
54
0
Order By: Relevance
“…Perhaps to buffer the effects of racial discrimination on psychological wellbeing, social support needs to be specific for experiences of racial discrimination. In support of this notion, social support tailored for racial discrimination, but not general social support, has been shown to buffer the negative effects of racial discrimination on depressive symptoms in non-pregnant African American women (Seawell et al, 2014). Therefore, in order for social support to be effective, it must match the needs elicited by the stressful situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps to buffer the effects of racial discrimination on psychological wellbeing, social support needs to be specific for experiences of racial discrimination. In support of this notion, social support tailored for racial discrimination, but not general social support, has been shown to buffer the negative effects of racial discrimination on depressive symptoms in non-pregnant African American women (Seawell et al, 2014). Therefore, in order for social support to be effective, it must match the needs elicited by the stressful situation.…”
Section: Discussionmentioning
confidence: 99%
“…Research with non-pregnant African American women also suggests that social support moderates the effect of racial discrimination on psychological wellbeing. Supporting the stress buffering hypothesis, one group of researchers found that African American women who received high levels of social support tailored for racial discrimination were protected from the negative impact of racial discrimination on depressive symptoms (Seawell, Cutrona, & Russell, 2014). In contrast, African American women who reported low levels of such tailored social support experienced the highest level of depressive symptoms (Seawell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnes and Lightsey () found that racial discrimination correlated to stress for Blacks and resulted in intrusive thoughts, images, feelings, and lower life satisfaction. Increases in racial discrimination over a 2‐year period increased depressive symptoms and decreased optimism (Seawell, Cutrona, & Russell, ). An association was found between discrimination and anger, showing that individuals who experience racial discrimination report higher levels of anger (Edmond, Granberg, Simons, & Lei, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Black women engage additional social resources that ameliorate the effect of PTSD on alcohol misuse or that social norms regarding drinking are strongly negative in Black women overall. Few studies have examined these relationships among Black women specifically and have focused mainly on depression or distress [105108]. In a study of Black families [109], for example, distress (general anxiety and depression symptoms) partially mediated the discrimination-substance use relationship.…”
Section: Discussionmentioning
confidence: 99%